PERAN KEPALA DESA DALAM MENINGKATKAN KINERJA APARATUR BIDANG PENGELOLAAN DANA DESA DI DESA LEBAKBARANG KECAMATAN LEBAKBARANG KABUPATEN PEKALONGAN PROVINSI JAWA TENGAH - Rachmat, Basuki (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2020)
Villages received very serious attention from the Government, with the Government issuing and enacting Law number 6 of 2014, on Villages, as well as establishing Village financial assistance, which is budgeted and allocated in the state budget annually. This financial assistance increases every year in line with the needs and problems of the current village. So the impact of that is where the Village Government in this case the Village Head and his staff must be able to manage the Village Fund effectively and efficiently, and transparently, in order to realize the accountability of Village Fund management. The researcher is interested in the extent to which the role of the village head can improve the performance of village fund management apparatus in the village of Tegalbarang, Tegalbarang sub-district. Tegalbarang village, a few years earlier was included in the IDM category which was lagging behind, with the financial assistance of the Village, the Village and the Village community could utilize the Village Fund to develop the Village Development Infrastructure, so that now Tegalbarang Village was included in the developing Village category based on the Regulation of the Ministry of Disadvantaged Regions number 6 years 2016, and in 2017, Tegalbarang Village is included in the developing village category. This study uses a descriptive qualitative method, with an inductive approach, with the theory used in this study is the Role theory, and related to the apparatus performance theory, as well as theories about the Village and Village Fund management. Conclusions can be explained that with the Prannya Village Head as the person in charge of Village Fund management, where the management is carried out by following and based on the District Head Regulation number 100 of 2017, on Guidelines for Village Financial Management, the performance of the Village apparatus in Village Fund management can be said to be very good, and the constraints that arise can be overcome by deliberation between the Village, the Camat and the Village Facilitation that conducts assistance for the Village Fund assistance in Tegalbarang Village.